Regional Development in Africa 2020
DOI: 10.5772/intechopen.87192
|View full text |Cite
|
Sign up to set email alerts
|

The Factors Influencing SMEs Growth in Africa: A Case of SMEs in Zimbabwe

Abstract: Today Africa reports high levels of unemployment among other social issues causing governments' instability and low economic growth. Brain drain, low gross domestic product (GDP) per capita and growth reported across the continent requires an initiative on driving entrepreneurship development. The study seeks to investigate the determinants of small to medium enterprises (SMEs) growth in developing countries with a special focus on Zimbabwe. Informed by literature, the Zimbabwe Finscope Business Consumer Surve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 19 publications
0
13
0
Order By: Relevance
“…By entrepreneurial incapacity, the author meant that entrepreneurs lacked the skills, knowledge and aptitude to both form and nurture a successful business. Regarding Zimbabwe, recent studies (Majukwa 2019;Njanike 2019) on SMEs confirmed the critical role played by managerial expertise in sustaining SME profitability. However, the aforementioned studies, like many of their predecessors, tend to lump competencies together, hence precluding helpful and accurate feedback, and leads to questioning exactly what it means to attain competence (Norman, Norcini & Bordage 2014).…”
Section: Introductionmentioning
confidence: 93%
“…By entrepreneurial incapacity, the author meant that entrepreneurs lacked the skills, knowledge and aptitude to both form and nurture a successful business. Regarding Zimbabwe, recent studies (Majukwa 2019;Njanike 2019) on SMEs confirmed the critical role played by managerial expertise in sustaining SME profitability. However, the aforementioned studies, like many of their predecessors, tend to lump competencies together, hence precluding helpful and accurate feedback, and leads to questioning exactly what it means to attain competence (Norman, Norcini & Bordage 2014).…”
Section: Introductionmentioning
confidence: 93%
“…Manager's nancial literacy has a direct positive signi cant in uence on the performance of SMEs such as promoting e ciency and increasing market share and sales pro t(Agyapong & Attram, 2019). Education level of entrepreneurs positively in uenced net pro t(Gichuki et al, 2014) and SMEs pro tability(Njanike, 2020). The result of this study indicates that the use of credit increases the pro tability of agricultural MSEs by 22.7%, holding other factors constant.…”
mentioning
confidence: 69%
“…Informal learning is an unorganized and unsystematic view of education. It represents a spontaneous process that enables people to learn at a different pace (Njanike, 2019).The literature indicated a process that enables individual to learn at different pace, but it fails to mention if there are indices responsible for this e.g., socio-demographic characteristics and the extent to which individuals can learn at different pace. Notably, informal learning is void of rules and regulations and does not necessarily entail learning objectives usually covered by formal curricula (Harte, 2019), but rather, aims at the society at large with no imposition of obligation.…”
Section: B Informal Learning and Entrepreneurial Capacitymentioning
confidence: 99%
“…Entrepreneurial capacity plays a pivotal role in the case of SMEs (Njanike, 2019). It entails distinct elements such as passion, integrity, commitment, active learning and analysis, demonstration and practical, leadership and management.…”
Section: B Informal Learning and Entrepreneurial Capacitymentioning
confidence: 99%